Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

The coordinates of the preimage are:

[tex]\[
\begin{array}{l}
A(8,8) \\
B(10,6) \\
C(2,2)
\end{array}
\][/tex]

1. Reflect over [tex]\( y = -1 \)[/tex]. The new coordinates are:

[tex]\[
\begin{array}{l}
A'(8, \square) \\
B'(10, \square) \\
C'(2, \square)
\end{array}
\][/tex]

2. Reflect over [tex]\( y = -7 \)[/tex]. The new coordinates are:

[tex]\[
\begin{array}{l}
A''(8, \square) \\
B''(10, \square) \\
C''(2, \square)
\end{array}
\][/tex]

Note: [tex]\( -7 - (-1) = -6 \)[/tex].


Sagot :

Let's reflect the coordinates step-by-step according to the given instructions.

### Step 1: Reflecting Over [tex]\( y = -1 \)[/tex]

To reflect a point [tex]\((x, y)\)[/tex] over the line [tex]\(y = -1\)[/tex], we can use the formula:
[tex]\[ y' = -1 - (y - (-1)) \][/tex]
This simplifies to:
[tex]\[ y' = -1 - y + 1 = -y - 1 + 1 = -y - 2 + 2 - 1 = -2y -1 + 1 = -y + 1\][/tex]

Let's apply this to the coordinates of the points [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex].

1. Point [tex]\(A(8, 8)\)[/tex]:
[tex]\[ y'_A = -1 - (8 - (-1)) = -1 - (8 + 1) = -1 - 9 = -10 \][/tex]
So, [tex]\( A'(8, -10) \)[/tex].

2. Point [tex]\(B(10, 6)\)[/tex]:
[tex]\[ y'_B = -1 - (6 - (-1)) = -1 - (6 + 1) = -1 - 7 = -8 \][/tex]
So, [tex]\( B'(10, -8) \)[/tex].

3. Point [tex]\(C(2, 2)\)[/tex]:
[tex]\[ y'_C = -1 - (2 - (-1)) = -1 - (2 + 1) = -1 - 3 = -4 \][/tex]
So, [tex]\( C'(2, -4) \)[/tex].

The coordinates after reflection over [tex]\( y = -1 \)[/tex] are:
[tex]\[ \begin{array}{l} A'(8, -10) \\ B'(10, -8) \\ C'(2, -4) \end{array} \][/tex]

### Step 2: Reflecting Over [tex]\( y = -7 \)[/tex]

To reflect a point [tex]\((x, y)\)[/tex] over the line [tex]\(y = -7\)[/tex], we can use the formula:
[tex]\[ y'' = -7 - (y' - (-7)) \][/tex]
This simplifies to:
[tex]\[ y'' = -7 - y' + 7 = - y' \][/tex]

Let's apply this to the new coordinates:

1. Point [tex]\(A'(8, -10)\)[/tex]:
[tex]\[ y''_A = -7 - (-10 - (-7)) = -7 - (-10 + 7) = -7 - (-3) = -7+ 3 = -4 \][/tex]
So, [tex]\( A''(8, -4) \)[/tex].

2. Point [tex]\(B'(10, -8)\)[/tex]:
[tex]\[ y''_B = -7 - (-8 - (-7)) = -7 - (-8 + 7) = -7 - (-1) = -7+1 \][/tex]
So, [tex]\( B''(10, -6) \)[/tex].

3. Point [tex]\(C'(2, -4)\)[/tex]:
[tex]\[ y''_C = -7 - (-4 - (-7)) = -7 -(-4+7)= -7 -3 \][/tex]
[tex]\[ y''_C =4+(-7-\sqrt{36}) \][/tex]
So, [tex]\( C''(2, -10) ). The final coordinates after reflection over \( y = -7 \)[/tex] are:
[tex]\[ \begin{array}{l} A''(8, -4) \\ B''(10, -6) \\ C''(2, -10) \end{array} \][/tex]

Thus, the values of [tex]\( y' \)[/tex] for points [tex]\(A\)[/tex], [tex]\(B\)[/tex], and [tex]\(C\)[/tex] are [tex]\(-10\)[/tex], [tex]\(-8\)[/tex], and [tex]\(-4\)[/tex] respectively, and the final reflected coordinates are [tex]\(A''(8, -4)\)[/tex], [tex]\(B''(10, -6)\)[/tex], and [tex]\(C''(2, -10)\)[/tex].